Investigation of nutritional content and aflatoxin B1 in landraces and varieties of Ethiopian groundnut (Arachis hypogaea L.) - Syraji Yonas; K. Gobikanila; P. R. Jeyaramraja (Discover Food)
Abstract Aflatoxins, a group of toxic compounds produced by certain Aspergillus species, pose significant health risks due to their strong carcinogenic properties. Groundnut (Arachis hypogaea L.) is susceptible to aflatoxin contamination both pre- and post-harvest. This study aimed to investigate the nutritional content and aflatoxin B1 (AFB1) levels in various landraces and varieties of Ethiopian groundnut. Groundnut germplasm was collected from three key regions: Gamo zone, Haramaya University (Haramaya), and Werer Agricultural Research Center (Werer). Key parameters, including individual seed weight (ISW), kernel colonization by Aspergillus flavus, total carbohydrates, protein, total free amino acids, and AFB1 content, were analyzed. The results revealed significant variation (P < 0.05) among the landraces and varieties. The groundnut varieties from Haramaya exhibited significantly higher mean ISW. All five varieties from Haramaya showed zero percent kernel colonization by A. flavus, indicating certain level of resistance. Landraces from Gamo zone were found to be rich in total carbohydrates and total free amino acids. AFB1 levels, determined using indirect competitive ELISA, ranged from 1.84 ppb to 6.89 ppb. While four landraces from Gamo, two varieties from Haramaya, and five varieties from Werer met the European Union’s AFB1 safety threshold (2 ppb), the remaining germplasm exceeded this limit, posing health and trade concerns. No relationship was found between nutritional content and AFB1 levels; however, a significant correlation was observed between kernel colonization and AFB1 content, suggesting kernel colonization could serve as a cost-effective proxy for estimating AFB1 contamination in groundnuts.